Implementasi Pilar Pembangunan Sosial Sustainable Development Goals (SDGs) Melalui Kegiatan-Kegiatan di Sekolah Dasar - Mujab, Bangkit Saiful; Nugraheni, Nursiwi (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Sustainable Development Goals (SDGs) is the agenda that must be supported by all elements, including in education field. The research aimed to explore the implementation the pillars of social development of SDGs through the programs in elementary school. The research was located in Elementary State School of Wonodri, South Semarang District, Semarang City. In this research used qualitative method that used case study as approach method. Futhermore, the data was collected by using documentation and direct observation technique. The result indicated that the implementation of social pillar of SDGs in elementary school were realizing Healthy and Prosperous Life by holding Friday Cleaning every once a month and Collaborating with Public Health Center to educate the students to maintain good health. Then, there was implemetation of Gender Equality, in which women students’ engagement in school activity, such as making them as leader of the ceremony. Meanwhile, in the implementation of Quality Education Goals, the school has been equipped the tools and infrastructure that support the learning process, such as the using of LCD in the learning, procuring fans in every classroom, and having professional teachers who understand student characteristics and teach with many inovative and creative activity.